Amino‐functionalized SiO2 modified porous polyetherimide separator for high performance Li‐S batteries. (17th August 2022) - Liu, Jiuqing; Zeng, Fanli; Liu, Meng; He, Junying; Li, Qihou; Song, Feifei; Hong, Zikun; Chen, Ya; Bai, Lishun; Cheng, Chen; Chen, Zehao
Summary: As one of the most promising energy storage systems, the application of lithium sulfur battery is hindered by low ionic conductivity, poor thermal stability, and a serious shuttle effect of polysulfide species of commercial polyolefin separators. Herein, a kind of novel porous polyetherimide (PEI) based separator (IAPEI‐4) with excellent heat resistance and electrochemical properties was prepared. Briefly, by grafting amino group (–NH2 ) onto the surface of SiO2, highly dispersed amino‐functionalized SiO2 (A‐SiO2 ) were synthesized as fillers to blend PEI matrix. Based on physical characterizations of the representative IAPEI‐4 separator, abundant micropores and mesopores exist in the separator, and A‐SiO2 nanoparticles are uniformly distributed in the PEI matrix. The ameliorated Li + transport channels and the uniform distribution of A‐SiO2 nanoparticles endow IAPEI‐4 separator with higher ionic conductivity (1.60 mS cm −1 ) and Li + transfer number (0.63). Besides, the IAPEI‐4 separator exhibits good electrochemical stability and excellent thermal stability (no shrinkage at 200°C). The Li‐S cells with the IAPEI separator also show greatly enhanced electrochemical performances. After 100 cycles, its specific discharge capacity can reach 695.4 mAh g −1 at 0.2 C and its capacity retention rate is 84.8%. This simple and effective separator modification method can provide a general strategy to achieve high‐performance Li‐S batteries. Abstract : In this work, by synthesizing highly dispersible amino‐functionalized SiO2 as fillers to blend PEI matrix, a kind of polyetherimide (PEI) based separator was prepared via a simple non‐solvent induced phase separation method. The as‐prepared separator possesses enhanced transport properties of lithium ions, good electrochemical stability, and excellent thermal stability. In addition, the modified separator can inhibit the polysulfide shuttling and promote uniform Li deposition. Therefore, the Li‐S cells with IAPEI‐4 separator exhibit good electrochemical performance.